Parental Beliefs about Returns to Child Health Investments - Pietro Biroli; Teodora Boneva; Akash Raja; Christopher Rauh (Institute of Labor Economics (IZA), 2018)
Childhood obesity has adverse health and productivity consequences and poses negative externalities to health services. Its increase in recent decades can be traced back to unhealthy habits acquired in the household. We investigate whether parental beliefs play a role by eliciting beliefs about the returns to a recommended-calorie diet and regular exercise using hypothetical investment scenarios. We show that perceived returns are predictive of health investments and outcomes, and that less educated parents perceive the returns to health investments to be lower, thus contributing to the socioeconomic inequality in health outcomes and the intergenerational transmission of obesity.
Keywords: D19; I10; I12; I14; 330; parental investments; health; beliefs; inequality; equality of opportunity; obesity